SOSIO-TEOLOGIS: Konsep Umat Pilihan Allah dalam Penaklukan Bangsa Kanaan (Ul 7:1-11) sebagai Representatif Sikap Gereja terhadap Pluralitas - Bara Izzat Wiwah Handaru (LPPM STT Baptis Kalvari, 2021)
The concept of Israel as “God's Chosen People” has become a predicate for the church, as the embodiment of its identity and existence. However, amidst the challenges of religious pluralism, sociocultural and the reality of multiculturalism today, the concept of God's chosen people is under very strong pressure. Although it aims to show its existence and identity in real terms, the reactions that appear tend to refer to an exclusive religious attitude ever assessing its social relations with other religions.In Deuteronomy 7: 1- 11, its contextual relevance to the life of the Church in the context of a plural society is not on the uniqueness of God's chosen people “that God has chosen Israel” (verse 6) but on